2003
DOI: 10.1046/j.1525-1314.2003.00449.x
|View full text |Cite
|
Sign up to set email alerts
|

Petrological constraints on the formation conditions and retrograde P–T path of the Kotsu eclogite unit, central Shikoku

Abstract: A largely undocumented region of eclogite associated with a thick blueschist unit occurs in the Kotsu area of the Sanbagawa belt. The composition of coexisting garnet and omphacite suggests that the Kotsu eclogite formed at peak temperatures of around 600 °C synchronous with a penetrative deformation (D1). There are local significant differences in oxygen fugacity of the eclogite reflected in mineral chemistries. The peak pressure is constrained to lie between 14 and 25 kbar by microstructural evidence for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
61
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 26 publications
7
61
2
Order By: Relevance
“…12). Similar relationship between the mode of occurrence and chemical composition of phengite has been reported from an eclogite in the Kotsu area, eastern Shikoku (Matsumoto et al, 2003). In the Kotsu eclogite phengite grains lying within the schistosity show a distinct chemical zonation with the celadonite rich rim composition close to the composition of the phengite replacing the garnet and a more celadonite poor core.…”
Section: Choice Of Equilibrium Compositionssupporting
confidence: 77%
“…12). Similar relationship between the mode of occurrence and chemical composition of phengite has been reported from an eclogite in the Kotsu area, eastern Shikoku (Matsumoto et al, 2003). In the Kotsu eclogite phengite grains lying within the schistosity show a distinct chemical zonation with the celadonite rich rim composition close to the composition of the phengite replacing the garnet and a more celadonite poor core.…”
Section: Choice Of Equilibrium Compositionssupporting
confidence: 77%
“…The peak pressures estimated for the Highashi-akaishi body are consistent with 2.3 -3.7 GPa pressure estimates from an associated 100-m-scale enclave of kyanite-quartz eclogite [Enami, 2003] that lies on the NE margin of the Higashiakaishi body (Figure 1b) but are distinctly higher than those of other members of the Eclogite unit such as the Seba and Kotsu bodies [Aoya, 2001;Matsumoto et al, 2003]. The above petrological information suggests it is necessary to subdivide the Eclogite unit into two or more separate domains with distinct tectonic histories.…”
Section: Geological Settingsupporting
confidence: 74%
“…The presence of paragonite during prograde and retrograde conditions shows that peak pressure in at least some members of the Eclogite unit did not exceed 2.3 GPa [Aoya, 2001, Matsumoto et al, 2003. Detailed structural studies of the eclogite bodies reveal a pre-Ds deformation history distinct from the Besshi unit [Aoya and Wallis, 1999].…”
Section: Geological Settingmentioning
confidence: 94%
“…Abbreviations of rock-body names other than KT (Kotsu) follow Fig.3. Petrologically derived P-T paths (Mizukami & Wallis (2005) for HA, Endo (2010) and Endo et al (2012) for WI, Aoya et al (2003) and Weller et al (2015) for KT, and Enami (1998) for the Shirataki unit are shown by bold arrows, and those derived using thermal model of Endo et al (2012) by dashed bold arrows. (a) 117-109 Ma.…”
Section: Fettes and Desmons 2007mentioning
confidence: 99%
“…Other 3 results of ridge-approach model by Iwamori (2000), which incorporates mantle convection at depths >30 km and uses v = 6.3 cm/year, are shown by dashed bold lines labeled by the corresponding ages of the slab at trench, 2.5, 1.0 and 0 Ma. Katayama et al 2001 540 Ma Okamoto et al 2004-Miyamoto et al, 2007 ; Engebretson 89 Ma Okudaira and Yoshitake, 2004Nakajima et al, 1990;, 1991;Otsuki, 1992;, 1993;Sakaguchi, 1996;Maruyama et al, 1997;Iwamori, 2000;Aoya et al, 2003Wallis et al, 2009Nakajima et al, 2004aNakajima et al, 1990;, 199385-80 Ma Wallis et al, 2009Taira et al, 2016 89 Ma 86 Ma…”
Section: Fettes and Desmons 2007mentioning
confidence: 99%